Accurate geometric correction for NOAA/AVHRR data - HUANG Jing-feng; XU Hong-wei; WANG Ren-chao; JIANG Heng-xian (浙江大学学报. 农业与生命科学版, 2000)
It was pointed out in this paper that accurate geometric correction is the presupposition of rice growth monitoring and yield estimation using NOAA/AVHRR data at province level, therefore it is necessary to select an accurate geometric correction method which should be easy to use for non-professional users and to assure the accuracy. After the standard space was established using ARC/INFO and ENVI function and a lot of images transform and enhancement was performed, the ground control points were selected. The combined RMSs were calculated for 59 NOAA/AVHRR data of Zhejiang province, The result of variance ahalysis and multiple comparisons showed that the RMSs differences of RST, 1st degree polynomial and 2ed polynomial warping methods were significant. At last, the 2ed polynomial warping methods was selected as accurate geometric correction method and cubic convolution re-sampling method was available for sub-image of NOAA/AVHRR data for rice growth monitoring and yield estimation.